Transformasi Digital: Strategi Pengembangan Sumber Daya Manusia di Era Modern - Farha Auliya Az – Zahra; Muhammad Hilman Fratama; Machdum Bachtiar (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Digital technology has fundamentally transformed human resource development (HRD), shifting organizations from conventional face-to-face training toward technology-enabled learning systems that enhance efficiency and workforce adaptability. This study explores the role of digital technology in HR strategies using a qualitative library research approach, drawing on relevant literature related to Industry 4.0 and digital transformation. Human resources remain the key driver of organizational success, yet traditional development methods are increasingly inadequate in responding to rapid business changes, globalization, and knowledge advancement. Effective HR management requires continuous competency development that integrates knowledge, skills, attitudes, and behaviors aligned with organizational goals. In this context, digital transformation plays a crucial role by introducing tools such as Learning Management Systems (LMS), e-learning, microlearning, Artificial Intelligence (AI), and Human Resource Information Systems (HRIS). These technologies enable flexible learning access, real-time data analysis, and personalized training. The implementation of digital technology in HRD offers several advantages, including cost efficiency, scalability, faster knowledge transfer, and more objective performance evaluation. It also supports the creation of a continuous learning culture and enhances organizational competitiveness. However, challenges such as limited digital literacy, high infrastructure costs, data privacy issues, and resistance to change must be addressed. In conclusion, digital technology has transformed HRD into a strategic function that supports organizational resilience. Its successful implementation requires strong leadership commitment, adaptive organizational culture, and readiness of human resources to ensure sustainable competitive advantage